Effects of Sudden and Violent Spousal Loss on Grief and Trauma Responses among Bereaved Partners - Adaobi Jennifer Iloakasia; Tiara Agustine (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Losing a spouse is one of life’s most devastating experiences, particularly when the loss occurs suddenly or through violence. The mode of death can significantly shape the bereavement process and emotional recovery. Objective: This study aimed to examine differences in grief and trauma responses among bereaved partners who experienced either sudden or violent spousal loss. Method: The research employed a descriptive survey design and was conducted in Anambra State, Nigeria, with 67 purposively selected participants aged 18 and above. Data were collected via a structured online questionnaire that included demographic items and standardized grief and trauma measures (reliability coefficients α = 0.87 and α = 0.89, respectively). The analysis utilized SPSS v25, including descriptive statistics, independent t-tests, and MANOVA, with a 0.05 significance level. Results: Individuals who experienced violent spousal loss reported significantly higher levels of grief, including emotional numbness (M = 3.40), a sense of life being meaningless (M = 3.70), and social isolation (M = 3.30) compared to those who experienced sudden loss, t(65) = -2.15, p = .036. However, trauma levels did not differ significantly between the groups (p = .577). Distinct patterns emerged: violent loss was associated with emotional detachment and concentration difficulties, while sudden loss was linked to more frequent unwanted memories. Conclusion: The study concludes that the nature of spousal loss has a greater impact on grief than trauma. These findings suggest that grief responses vary significantly depending on whether the loss was sudden or violent. Contribution: The findings contribute to the development of more effective emotional care strategies for the bereaved, ensuring that interventions are better suited to the emotional needs of individuals experiencing different types of spousal loss.